Right Breast Mastectomy and Reconstruction with Tissue Expander under Thoracic Paravertebral Blocks in a 12-Week Parturient. (2nd July 2015) - Webb, Christopher Allen-John; Weyker, Paul David; Cohn, Shara; Wheeler, Amanda; Lee, Jennifer
Abstract : Paravertebral blocks are becoming increasingly utilized for breast surgery with studies showing improved postoperative pain control, decreased need for opioids, and less nausea and vomiting. We describe the anesthetic management of an otherwise healthy woman who was 12 weeks pregnant presenting for treatment of her breast cancer. For patients undergoing breast mastectomy and reconstruction with tissue expanders, paravertebral blocks offer an anesthetic alternative when general anesthesia is not desired.